2007
DOI: 10.33573/ujoh2007.04.071
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Occupational Asthenopia and the Psychophysiological Indicators of Visual Fatigue for VDT Workers

Abstract: Januskevicius Vidm antas2 'D e p a rtm e n t o f En viron m en ta l and O cc u p a tio n a l M e dicin e , K a u n a s U n ive rs ity o f M e dicin e , Lithuania, d e p a r t m e n t o f H ealth S y s te m s R e se a rc h o f Institute o f Biom edical R e se arch , K a u n a s U n ive rs ity o f M e dicin e , Lithuania To evaluate the relationship o f functional visual fatigue parameters with the symptoms o f asthenopia, and to determine associ ation between subjective and the objective indicators o f eye fati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, a smaller pupil may reduce ocular aberrations and the amount of light scatter [46], while improving the depth of focus, which would reduce the accommodative strain. We think that these may be some of the reasons why the literature presents contradictory findings on the evaluation of the relationship between CVS and age [47].…”
Section: Discussionmentioning
confidence: 94%
“…However, a smaller pupil may reduce ocular aberrations and the amount of light scatter [46], while improving the depth of focus, which would reduce the accommodative strain. We think that these may be some of the reasons why the literature presents contradictory findings on the evaluation of the relationship between CVS and age [47].…”
Section: Discussionmentioning
confidence: 94%
“…This finding suggests that many individuals perceive diplopia and blurred vision following computer use. 2 , 19 , 39 Earlier studies have shown that stereoacuity is best under photopic and is reduced under mesopic and scotopic conditions. 40 , 41 We set the illumination of BFM test and visual task at 270 lx.…”
Section: Discussionmentioning
confidence: 99%
“…Diplopia is the subjective complaint of seeing two retinal images of the single object and is one of the most prevalent visual symptoms associated with visual fatigue in nonstrabismic computer workers. 19 This is caused by the deviation of one eye to heterophoric posture (eso- or exo- deviation) when sensory and motor fusion are diminished 20 ; therefore, the ability to maintain binocular fusion, which merges two retinal images in the brain, 21 may be an objective parameter to represent visual fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…(17,18) There is currently a relative paucity of clinical evidence to support many claims surrounding the deleterious effects of blue-light exposure. (19) Although ocular discomfort symptoms have been long associated with computer and video display terminal use, (20,21) the relative contribution of blue light per se (rather than other potential causative factors, such as binocular vision anomalies, postural factors, and/or tear film dysfunction) remains unclear. (19) However, in this investigation, the subjects had their refractive errors properly corrected and did not present oculomotor diseases or accommodative or converge problems.…”
Section: Discussionmentioning
confidence: 99%